RELASI KEKUASAAN ANTARA PEMERINTAH DAERAH DENGAN KERAJAAN GOWA DALAM MELESTARIKAN DAN MENGOPTIMALKAN NILAI BUDAYA DI KABUPATEN GOWA - Sri Sumarni Sjahril; Gustiana Kambo; Muhammad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This research aims to of find out the power-relationship between the Government of theGowa Regency and the Kingdom of Gowa in preserving and optimizing the value ofculture in Gowa Regency. This research uses a qualitative method with a descriptiveapproach. The data used in this research is was primary data obtained from interviewsand secondary data collected through library study and documentation. The method ofdata analysis used descriptive method obtained from the interviews based on thetheoretical framework used in this research the theory used was the concept of Politicalpower. The research results show that The unequal power relationship created regionalgovernment's dominance in the management and strengthening of cultural values byissuing the regional customary institution regional regulation of Gowa Regency Number5 Year 2016 and placing the Regents as the Chairman of the regional customaryinstitution who runs the function and role of Sombayya. This makes the royal descendentno longer able to run the function and role of the Sombayya in preserving the culturalvalues of Gowa Regency.